A comparative study on clinical characterizations between acute myelitis onset of neuromyelitis optica spectrum disease and idiopathic transverse myelitis. (2nd July 2020) - Liu, Zhuo; Xie, Meixin; Lu, Zhengjuan; Zhang, Cunjin; Chen, Huiping; Xu, Yun; Zhang, Meijuan
ABSTRACT: Background/Aims: Both of neuromyelitis optica spectrum disease (NMOSDs) and idiopathic transverse myelitis (ITM) could present as acute transverse myelitis. However, long-term immunological treatment and prognosis are different for high recurrence of NMOSDs. In this study, we summarized clinical differences between acute attack myelitis of NMOSDs and ITM, we further screened serum auto-antibodies to help understand the two distinct clinical entities. Methods: This is a retrospective study on 48 NMOSD patients and 49 ITM patients in neurological department of Nanjing Drum Tower Hospital from 2013 to 2019. Clinical, CSF and MRI profiles on the acute episode were also compared between NMOSD patients and ITM patients. Serum AQP4 and auto-antibodies were tested. Clinical parameters were further compared between NMOSD patients with and without auto-antibodies. Results: Compared with ITM patients, NMOSD patients manifested with longer vertebral segments (5.42 ± 3.17 segments vs . 2.31 ± 2.36 segments, p < 0.001), higher female/male ratio (13:3 vs . 20:29, p < 0.001), higher IgG index (30.30% vs . 9.09%, p < 0.05). Positive rates of anti-Ro-52 (47.92% vs . 14.29%, p < 0.001), anti-ANAs (50.00% vs .10.20%, p < 0.001) and anti-SSA (35.42% vs . 6.12%, p = 0.001) were significantly higher in the NMOSD patients than the ITM patients. Seropositive Ro-52 and SSA were associated with longer injured spinal cord segments. However, Ro-52 antibody may not be associated with NMOSD relapsing during our follow up. Conclusions: NMOSD patients manifested with longer vertebral segments, higher female/male ratio, IgG index, anti-ANAs, anti-Ro-52 and anti-SSA seroprevalence than ITM patients. These features may help clinicians better distinguish NMOSD from ITM and provide long-term immunotherapy reasonably.